Activated Ezrin Promotes Cell Migration through Recruitment of the GEF Dbl to Lipid Rafts and Preferential Downstream Activation of Cdc42 - Prag, Soren (The American Society for Cell Biology, 2007)
Establishment of polarized cell morphology is a critical factor for migration and requires precise spatial and temporal activation of the Rho GTPases. Here, we describe a novel role of the actin-binding ezrin/radixin/moesin (ERM)-protein ezrin to be involved in recruiting Cdc42, but not Rac1, to lipid raft microdomains, as well as the subsequent activation of this Rho GTPase and the downstream effector p21-activated kinase (PAK)1, as shown by fluorescence lifetime imaging microscopy. The establishment of a leading plasma membrane and the polarized morphology necessary for random migration are also dependent on ERM function and Cdc42 in motile breast carcinoma cells. Mechanistically, we show that the recruitment of the ERM-interacting Rho/Cdc42-specific guanine nucleotide exchange factor Dbl to the plasma membrane and to lipid raft microdomains requires the phosphorylated, active conformer of ezrin, which serves to tether the plasma membrane or its subdomains to the cytoskeleton. Together these data suggest a mechanism whereby precise spatial guanine nucleotide exchange of Cdc42 by Dbl is dependent on functional ERM proteins and is important for directional cell migration.